Analisis Persepsi Konsumen terhadap Harga dan Kualitas Produk dalam Keputusan Pembelian Dimsum Goreng - Miya Dewi S; Javier Ikrom Aquino; Yohana Gardi Sefrin; Suci Sekar Arum S.A; Aisyah Rafifah Nabila (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Business competition in the culinary sector continues to increase along with changes in people's consumption patterns towards ready-to-eat food. One product that is quite popular is fried dim sum, which is known for its variety of flavors and relatively affordable prices. In this competitive environment, understanding how consumers perceive product price and quality is crucial for businesses to maintain and increase customer interest in purchasing goods. Consumer perceptions of product price and quality when they choose fried dim sum are the subject of this study. Informants were selected purposively in this study, which used a qualitative and descriptive approach, namely consumers who have purchased and consumed fried dim sum products. Data collection methods included comprehensive interviews, direct observation, and supporting documentation. The collected data were analyzed using an interactive analysis model developed by Miles and Huberman through steps such as data reduction, data presentation, and discovery. The results show that consumers view price as an indicator related to the affordability and suitability of the product value. Price is considered acceptable if it is commensurate with perceived quality. In addition, product quality, including taste, texture, cleanliness, and packaging, is a primary factor considered before making a purchase. Positive perceptions of product quality increase customer trust and encourage repeat purchases. This study concluded that customer perceptions or opinions about price and product quality influence fried dim sum purchasing decisions. Therefore, culinary businesses need to prioritize proportional pricing and maintain consistent product quality to enhance business competitiveness.